2021
DOI: 10.3390/agronomy11122408
|View full text |Cite
|
Sign up to set email alerts
|

Modern Short Food Supply Chain, Good Agricultural Practices, and Sustainability: A Conceptual Framework and Case Study in Vietnam

Viet Hoang

Abstract: The rapid increases in environmental pollution, urbanization, health concerns, and technological progress enhance the demand for greener, healthier, and fairer food production and consumption. The short food supply chain (SFSC) becomes one of the crucial solutions for these issues. This study aims to propose a conceptual framework of the SFSC, assess the short vegetable supply chain (SVSC) in Vietnam, identify its barriers and challenges, and explore interventions and support as key success factors of the SVSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…While mainstream food systems struggled to cope, local foods saw a marked increase in consumer demand. Hoang (this issue) [23] discusses how the renewed interest in short food supply chains is not only reconnecting consumers to food producers, but also providing smallholder farmers with a more fair and equitable proportion of the retail price, increasing their profitability, revitalizing local communities, and supporting farmers in their efforts to adopt more sustainable and ethical food production systems. However, the participation of smallholder farmers in these short food supply chains is constrained by many impediments, including the small scale of production; the higher costs of sustainable production; a smaller output market; a lack of credit; the lack of capacity; and, just as Constantin et al [18] noted, with a gradual shift in the political regime in Viet Nam, farmers' unwillingness to cooperate.…”
Section: Urban Food Systems In Action: a Summary Of The Papers Presen...mentioning
confidence: 99%
“…While mainstream food systems struggled to cope, local foods saw a marked increase in consumer demand. Hoang (this issue) [23] discusses how the renewed interest in short food supply chains is not only reconnecting consumers to food producers, but also providing smallholder farmers with a more fair and equitable proportion of the retail price, increasing their profitability, revitalizing local communities, and supporting farmers in their efforts to adopt more sustainable and ethical food production systems. However, the participation of smallholder farmers in these short food supply chains is constrained by many impediments, including the small scale of production; the higher costs of sustainable production; a smaller output market; a lack of credit; the lack of capacity; and, just as Constantin et al [18] noted, with a gradual shift in the political regime in Viet Nam, farmers' unwillingness to cooperate.…”
Section: Urban Food Systems In Action: a Summary Of The Papers Presen...mentioning
confidence: 99%
“…There are different groups of possible systems, including "community-supported agriculture" and "member states" (Todorova, 2020), and the main issues include direct communication (consumer-producer) and transportation (e.g., farm shops, pick-your-own). Jarzebowski et al (2020) classify factors into three groups: (1) creation of short food supply chains (product know-how, innovations, regulatory frameworks and government policies); (2) product development in the short food supply chain (efficient application of technology, investment of time and money, collective branding); and (3) access to market (online sales, sales to local communities) (Hoang, 2021). Sellitto et al (2018) have identified nine factors present in the short food supply chain: environmental friendliness of operations; specificity of territorial brands; direct and ethical relationships between producers and consumers; organic production; food safety and traceability; cultural heritage; consumers' health; origin identification of products; and local work and cooperation.…”
Section: A Brief Literature Review On the Nexus Between Food Security...mentioning
confidence: 99%
“…SFCSs aim at reducing the “distance” between agriculture and final consumption, directly re-connecting farmers to consumers and contributing towards the sustainability of food systems (Jarzebowski et al , 2020). SFSC empowers farmers to play active roles in food value chains and enables small-scale producers to create independent food supply chains, resulting in fair prices and strong local economies (Hoang, 2021).…”
Section: Literature Review: Agritourism and The Local Food Systemmentioning
confidence: 99%